2021
DOI: 10.15398/jlm.v9i1.262
|View full text |Cite
|
Sign up to set email alerts
|

Typology emerges from simplicity in representations and learning

Abstract: We derive well-understood and well-studied subregular classes of formal languages purely from the computational perspective of algorithmic learning problems. We parameterise the learning problem along dimensions of representation and inference strategy. Of special interest are those classes of languages whose learning algorithms are necessarily not prohibitively expensive in space and time, since learners are often exposed to adverse conditions and sparse data. Learned natural language patterns are expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The restrictiveness generated by these complexity measures supplements the more general simplicity criterion of theoretical syntax; much as how the 'subset principle' (restrictiveness) supplemented the original evaluation metric (simplicity) (Berwick, 1985). Lambert et al (2021) demonstrated that the computational simplicity of learning mechanisms appears to have a major impact on the types of patterns found in natural language, including for syntactic trees, and so it seems to us well motivated to turn to the issue of the underlying processes that guide the generation of these structures.…”
Section: Compressionmentioning
confidence: 99%
“…The restrictiveness generated by these complexity measures supplements the more general simplicity criterion of theoretical syntax; much as how the 'subset principle' (restrictiveness) supplemented the original evaluation metric (simplicity) (Berwick, 1985). Lambert et al (2021) demonstrated that the computational simplicity of learning mechanisms appears to have a major impact on the types of patterns found in natural language, including for syntactic trees, and so it seems to us well motivated to turn to the issue of the underlying processes that guide the generation of these structures.…”
Section: Compressionmentioning
confidence: 99%
“…Many other subregular classes exist, but only these few will be discussed in this work. For more details, readers are referred to Lambert et al [19]. SF is star-free [20].…”
Section: Model-theoretic Factors and Related Formal Language Classesmentioning
confidence: 99%
“…The restrictiveness generated by these complexity measures supplements the more general simplicity criterion of theoretical syntax; much as how the 'subset principle' (restrictiveness) supplemented the original evaluation metric (simplicity) (Berwick 1985). Lambert et al (2021) demonstrated that the computational simplicity of learning mechanisms appears to have a major impact on the types of patterns found in natural language, including for syntactic trees, and 26 so it seems to us well motivated to turn to the issue of the underlying processes that guide the generation of these structures.…”
Section: Compressionmentioning
confidence: 99%